PENGUATAN LITERASI BAHASA ARAB MELALUI KEGIATAN PENGABDIAN MASYARAKAT UNTUK MENDORONG KETERAMPILAN MEMBACA DAN MENULIS SANTRI DI SULAWESI BARAT - Khaerun Nisa Nuur; Muhammad Yusuf; Baso Pallawagau; Mohamad Harjum; Afifuddin; Muhammad Saleh; Muhammad Nur Abduh; Moh Rafli (LPPM STAI Muhammadiyah Probolinggo, 2025)
This research focuses on efforts to improve Arabic literacy skills among santri in West Sulawesi by integrating a community service approach. Through collaboration between pesantren, communities, and various related parties, this research examines the impact of such collaboration on Arabic reading and writing skills. Using a qualitative approach and case studies of two Islamic boarding schools, data were collected through interviews, observations, and documentation. The findings show that the community service-based approach has successfully promoted the improvement of santri's Arabic literacy skills, with a significant contribution of pesantren and community collaboration in the quality of learning. This research confirms the importance of sustainable synergy between pesantren and communities in advancing Arabic literacy, which also has the potential to be applied in other areas with similar contexts.